INTENSITAS PENGGUNAAN SMARTPHONE DAN PERILAKU KOMUNIKASI (Studi Pada Pengguna Smartphone di Kalangan Mahasiswa Program Studi Ilmu Komunikasi Universitas Telkom) - Sharen Gifary; IK Nurhayati (Jurnal Sosioteknologi, 2015)
ABSTRACT               Smartphone is a new media in the communication process. Smartphones are no longer used only for communication media but also to be considered by some manufacturers to make the smartphone as a medium of entertainment and education. The purpose of this research is to investigate and examine the effect of the Smartphone use intensity against the communication behavior (a study of Smartphone users among communication program students in Telkom University). This research involves one independent and dependent variables. The independent variable is the Smartphone use intensity (X) using Ardianto dan Erdinaya (2004). The dependent one is the communication behavior (Y) using Edward E. Sampson (Katherin Miller:2001). The primary data were collected through survey method with purposive sampling method using questionnaire given to 100 respondents. The type of this research was causal and descriptive with the research method of quantitative research. The data analysis technique was simple regression analysis. The results of the study showed that partially and simultaneous intensity of use of Smartphones effected significantly to the communication behavior in the amount of 55,4 % and the rest of 44,6 % was affected by other factors which are not examined in this research..